PEMANFAATAN PENGGUNAAN VIDEO INTERAKTIF ANIMASI DALAM PEMBELAJARAN TEKS BERITA PADA SISWA KELAS XI SMAN 1 GALIS - Nurul Kiptiyah; Liana Rochmatul Wachidah; Mochamad Arifin Alatas (Al-Amien Prenduan University, Sumenep, 2025)
The advancement of digital technology has had a substantial impact on the field of education, particularly in the strategies used by educators to deliver material in the classroom. This research aims to analyze and explain how interactive animation-based videos are used in news text learning for 11th-grade students at SMAN 1 Galis. The method applied is descriptive qualitative. data collection techniques thru observation and interviews at that school. Data sources include eleventh-grade students, Indonesian language teachers, and journal and book references. The research results show that the use of interactive animated video media is very effective in increasing students' enthusiasm and learning outcomes. This is because the teacher implemented several steps to maximize the use of this media in learning activities. The use of interactive animated videos in teaching news text also indirectly contributes to strengthening students' listening, speaking, and writing abilities. Therefore, this medium has a significant positive impact on learning news text among eleventh-grade students at SMAN 1 Galis.